Agroturism, a sustainable alternative for the rural sector in Floridablanca, Santander - Portilla Martínez, José Vicente (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of sustainable agrotourism in Floridablanca is to promote the recognition, protection and real exercise of the economic, social, cultural, political and environmental rights of the rural population, contributing to improve their well-being in terms of quality of life, social justice and access to labor rights of peasant communities. The analysis methodology is centered on dialogue and the projection of effective actions, with the participation of social actors. The strategies are the promotion of agrotourism, research, preservation and protection of biological diversity and improvement of the quality of life of the inhabitants.